Formulation, Evaluation and Optimization of Antimicrobial Potential of Herbal Cream Containing Allium sativum, Moringa oleifera Extracts and Thymus vulgaris Oil - Sheikh, Maliha; Khan, Humaira M.; Khan, Muhammad U.Z.; Sharif, Ali (Current Pharmaceutical Biotechnology, 2024)
Background: Herbal preparations can be formed by combining several plant classes. One possible explanation for the effectiveness of combined medications is that the various mixtures with different mechanisms may add up to produce a more comprehensive therapeutic effect. Objective: This study aims to investigate the synergistic antibiotic potential of a cream containing three natural herbal extracts: Allium sativum, Moringa oleifera, and Thymus vulgaris. The efficacy of combining these plant extracts was compared to that of a standard antibiotic formulation (Polyfax). Methods: The herbal cream was formulated by using aqueous extracts of garlic (Allium sativum), moringa (Moringa oleifera) and essential oil of thyme (Thymus vulgaris). The study aimed to explore the therapeutic potential of these extracts against bacteria. P. aeruginosa, B. subtilis, E. coli, S. aureus, and S. pneumonia are commonly found in fresh wounds. Results: The results showed that garlic extract (5%) had the highest zone of inhibition, 14.26 ± 0.05 mm, and a combination of garlic (5%) and thyme (2%) exhibited a significant synergistic effect, with a 23.5 ± 0.05 mm zone of inhibition. High-performance liquid chromatography analysis revealed the presence of allicin, quercetin and thymol as potential therapeutic phytoconstituents. The formulated herbal cream had a soft texture, was easily spreadable, and had better stability and absorption than the standard polyfax. The topical application of the cream did not cause any skin reaction or allergy in mice. The in vivo wound healing effect of the herbal cream was investigated on an abrasion model of albino mice, and the results showed that the treatment group (46 ± 16.31%) had significant wound healing potential compared to the standard (64 ± 17.49%) and control groups (18 ± 3.74%). Conclusion: The formulated herbal cream was a better alternative to standard therapy, exhibiting promising healing and antimicrobial effects with significant compatibility and safety profile.
Keywords: Wound healing